2019
DOI: 10.1038/s41598-019-52116-6
|View full text |Cite
|
Sign up to set email alerts
|

Study of Periodontal Health in Almada-Seixal (SoPHiAS): a cross-sectional study in the Lisbon Metropolitan Area

Abstract: This study aimed to describe the prevalence and extent of periodontal diseases among adults in the southern region of the Lisbon Metropolitan Area. This population-based cross-sectional study included 1,064 randomized participants (aged 18 to 95 years, 617 females/447 males). Sociodemographic, behaviours and medical information were recorded. Periodontal conditions were assessed with a full-mouth circumferential periodontal examination. It was used the American Association of Periodontology/European Federation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
4
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(72 citation statements)
references
References 44 publications
9
57
4
2
Order By: Relevance
“…A recent study from our group, including a representative sample of the population in the southern Lisbon Metropolitan Area, has shown one of the highest prevalences of periodontitis in Europe [28,29]. Almost 60% of the target population was estimated to have periodontitis, with 46% being moderate and severe cases [28]. Similarly, the prevalence of hypertension in Portugal was 36.0%, with higher estimates in males (39.6%) and among those aged 65 to 74 years (71.3%) [30], which exceeded the worldwide reported prevalence [31].…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…A recent study from our group, including a representative sample of the population in the southern Lisbon Metropolitan Area, has shown one of the highest prevalences of periodontitis in Europe [28,29]. Almost 60% of the target population was estimated to have periodontitis, with 46% being moderate and severe cases [28]. Similarly, the prevalence of hypertension in Portugal was 36.0%, with higher estimates in males (39.6%) and among those aged 65 to 74 years (71.3%) [30], which exceeded the worldwide reported prevalence [31].…”
Section: Introductionmentioning
confidence: 90%
“…A recent study from our group, including a representative sample of the population in the southern Lisbon Metropolitan Area, has shown one of the highest prevalences of periodontitis in Europe [28,29]. Almost 60% of the target population was estimated to have periodontitis, with 46% being moderate and severe cases [28].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…This measure, Bolton's analysis [31], only accounts for the mesiodistal width from the first molar to the first molar. Nevertheless, two previous large-base studies from this population revealed that second molars are one of the most commonly missing teeth, aside from first molars and premolars [32,33]. Interestingly, none of them accounted for the final model.…”
Section: Strengths and Limitationsmentioning
confidence: 70%
“…Dental prosthesis utilization was questioned and clinically confirmed (No = 0, Yes = 1). Clinical full-mouth periodontal examination was performed by two trained and calibrated investigators (VM and JB) (Botelho et al, 2019). For a more comprehensive description of the periodontal assessment, see Botelho et al (2019).…”
Section: Periodontal Treatment Needmentioning
confidence: 99%